Entheogenesis: Toward an Expanded Worldview for Our Time. (September 2017) - Metzner, Ralph
Whereas the terminology of psychedelics has acquired spurious cultural associations of "tripping, " the historically primal concept of consciousness expansion has two advantages. One, it connects psychedelic drugs with other modes of consciousness expansion, such as meditation and creative visioning; and two, it suggests contrasting comparison with the consciousness contraction involved in concentration and focus. Both expansions and contractions can be observed at the level of an individual's states of consciousness and also at the level of the shared worldview of society. Contemporary world culture is moving toward an expanded worldview that recognizes both the material and the spiritual dimensions of our existence.